Effectiveness of Vitamin C-Enriched Tubifex Worms (Tubifex sp.) as Live Feed for African Catfish (Clarias sp.) Larvae - Imam Tri Wahyudi; Sheny Permatasari; Andri Hendriana (Research and Social Study Institute, 2026)
Background: Live feed is a critical factor in the successful rearing of African catfish (Clarias sp.) larvae, particularly during the early developmental. Tubificid worms (Tubifex sp.) are commonly used as live feed due to their high protein content; however, their nutritional value can be further improved through enrichment techniques.Aims: This study evaluated the effects of vitamin C-enriched Tubifex worms on the growth performance and survival of African catfish larvae.Methods: A completely randomized design (CRD) consisting of three treatments and three replications was employed: unenriched Tubifex worms (control), enrichment with 2.5 g L⁻¹ vitamin C (A), and enrichment with 3.5 g L⁻¹ vitamin C (B). Data on survival rate (SR), specific growth rate (SGR), and growth rate (GR) were analyzed using one-way analysis of variance (ANOVA), followed by Duncan's multiple range test at a 95% confidence level. Seven-day-old larvae were reared for seven days and fed enriched worms according to the respective treatments. Growth performance was assessed using survival rate (SR), specific growth rate (SGR), and growth rate (GR).Results: The results showed that vitamin C enrichment significantly affected (P < 0.05) the survival rate, specific growth rate, and growth rate of African catfish larvae. The treatment enriched with 2.5 g L⁻¹ vitamin C produced the highest survival rate (86.67 ± 12.09%), specific growth rate (1.70 ± 0.66% day⁻¹), and growth rate (0.125 ± 0.055 g day⁻¹). These values were significantly higher than those of the control treatment and numerically higher than those of the 3.5 g L⁻¹ treatment.Conclusion: In conclusion, enrichment of Tubifex worms with vitamin C at 2.5 g L⁻¹ is an effective strategy for improving growth performance and survival of African catfish larvae and may be applied as a practical nutritional approach during the early rearing stage.